Memory and False Memory for Information That Is Either Expected or Unexpected Based on Age Stereotypes - Z. Asude Kaymak Gülseren; Simay İkier (Europe's Journal of Psychology)
Age is a major social categorization information because it is one of the first attributes that is perceived about an individual. The present study used the misinformation paradigm to investigate memory and false memory for information that is either expected or unexpected based on age stereotypes. Young adults were presented with a passage depicting a crime. The passage also contained information about the physical performance and social behavior of the main character that was either expected (expected information condition) or unexpected (unexpected information condition) for his age. The main character was a young adult in the expected information condition and an older adult in the unexpected information condition. Next, misinformation was provided about a detail related to the crime. After a non-verbal filler task, participants recalled the exact sentences from the passage, and then they completed a forced-choice recognition test for them. Measures of attitudes toward older adults did not differ across the groups. The results revealed worse recognition memory for the sentences and higher false recognition of the misinformation in the expected information condition than in the unexpected information condition. The recall test revealed higher commission errors in the expected information condition than in the unexpected information condition. Commission errors were in general consistent with the information in the passage. The results imply that stereotypically expected information is automatically processed, making it more vulnerable to memory errors. The study contributes to the understanding of the memory processes underlying stereotyping that can lead to prejudice and discrimination.